TAXONOMIC STUDIES ON CULTURAL AND MORPHOLOGICAL CHARACTERS FOR RE-EVALUATION IN HELMINTHOSPORIUM SPECIES COMPLEX - PRITI SONAVANE; T. PRAMEELA DEVI; J. RAJU (The Bioscan, 2015)
Fourty-two sporulating isolates of Drechslera, Helminthosporium, Bipolaris and Exserohilum obtained from Indian Type Culture Collection, New Delhi were used in this study. Macroscopic and microscopic studies revealed that, the isolates were assembled into two major groups and three sub-groups; there was a lot of variation in the cultural characters.In group I (28 isolates) aerial mycelium was fluffy, cottony and whitish gray in colour and there was wide variation in radial growth of the isolates [8.45 cm in D19 to 2.2 cm in D7]. In group II (14 isolates), most of the cultures were black in colour and texture was smooth in which radial growth was highest in E7 (8.65 cm) and lowest in D42 (6.25 cm). It was found that germination from two or more cells of conidia separates Drechslerafrom Bipolaris and Exserohilum. Whereas, presence of strongly protuberant hilum structure differentiates between Exserohilum and Bipolaris isolates. Thirteen of the isolates having strongly protuberant hilum structure were grouped into the genus Exserohilum. Remaining 29 isolates were considered as the genus Bipolaris group with no protuberant hilum.